OPTIMIZATION OF AFRICAN LEAF EXTRACT CREAM FORMULA (Vernonia amygdalina Del.) AS AN ANTIBACTERIAL Staphylococcus aureus - Iklila Zahra; Ana Indrayati; Ilham Kuncahyo (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
The use of natural ingredients as active medicinal substances has been developed again, one of which is African leaf extract (Vernonia amygdalina Del.), which is used as an antimicrobial bacterium against Staphylococcus aureus, which causes skin disease. The aim of this study was to compare the antibacterial activity of African leaf extracts and fractions, as well as to optimize the cream preparation formula using a factorial design with a combination of stearic acid, triethanolamine (TEA), and Adeps lanae with the critical parameters of pH, viscosity, spreadability, Franz diffusion, and KBM value. This study used experimental methods to determine the highest antibacterial activity by disc diffusion from extracts and active fractions of African leaves using solvents of different polarities. The extract or fraction with the highest antibacterial activity was formulated using a combination cream of stearic acid, triethanolamine, and adeps lanae. After obtaining the cream formula, physical testing of the cream, penetration test, and antibacterial test using macrodilution were performed, and the most optimal formula was determined using a factorial design. The extract standardization test results met both specific and non-specific parameters. In the disc diffusion antibacterial test, the highest activity was found in the African leaf extract (13.23 ± 0.757 mm) against Staphylococcus aureus bacteria. Variations in cream composition affect pH, viscosity, spreadability, and Franz diffusion...